Analisis Tingkat Kepuasan Pengunjung Perpustakaan Universitas Pekalongan - Dwi Susilo; Sugiarto Sugiarto (LPPM Universitas Pekalongan, 2017)
The Research entitle Analysis of Satisfaction Rate Library Visitors PekalonganUniversity, aims to find out how much the level of satisfaction of services made to library usershave coressponden with the expectations of library users, and to find out what kind of service isexpected by the visitors or users of the library and can already be met By the library manager. Thepopulation of research is all the members of Pekalongan University Librarry By using ImportancePerformance Analisys (IPA), it can be seen that all items of library management services uniquenot satisfactory, this can be seen from the value of visitor satisfaction level is still less than 100%and with the index of visitor satisfaction generated value 0.76, and this value is at interval 0.66 0.80if included in the Table Criteria of Visitor Satisfaction, it can be concluded that visitors feel